Exploratory software testing strategies for video games - Pessanha, Yohan Duarte (Universidade Federal de São Carlos, 2025)
The presence of bugs in video games can cause user frustration and negatively impact the commercial success of games. To prevent this, common software development practices can be applied to ensure the overall quality of the product. Similar to traditional software, testing is also necessary in games, with an emphasis on manual testing, especially when considering the player's perspective. A commonly used manual testing method is Exploratory Testing - an approach in which testers design and execute tests while simultaneously learning from the results to perform new test iterations. Despite the extensive literature on exploratory testing, there is a notable gap in discussions about its application in game testing. This can be a challenge for new testers, as they lack guides on how to effectively use exploratory testing in this domain. This thesis investigates exploratory testing for games. To achieve this objective, two studies were conducted. In the first study, we applied seven exploratory testing strategies known in the literature to five platform games. In the second study, we developed a framework for applying exploratory testing to platform games and conducted an applicability assessment using a platform game under development by an independent studio. The results were positive, with various bugs being identified, providing initial evidence that this adaptation is both viable and promising when considering the platformer genre.
Estratégias de teste exploratório de software para jogos digitais
Keywords: Bugs; Jogos digitais; Teste de jogos; Teste exploratório; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::ENGENHARIA DE SOFTWARE